2010
DOI: 10.4049/jimmunol.0902339
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and G1 Reduce Infarct Size and Improve Immunosuppression after Experimental Stroke

Abstract: Reduced risk and severity of stroke in adult females is thought to depend on normal endogenous levels of estrogen, a well-known neuroprotectant and immunomodulator. In male mice, experimental stroke induces immunosuppression of the peripheral immune system, characterized by a reduction in spleen size and cell numbers and decreased cytokine and chemokine expression. However, stroke-induced immunosuppression has not been evaluated in female mice. To test the hypothesis that estradiol (E2) deficiency exacerbates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 58 publications
5
82
0
1
Order By: Relevance
“…Although it is possible that there was a "floor" effect, this is unlikely as the residual infarct was still .30% of the ischemic hemisphere even after combination treatment, due to the length of the occlusion. Infarct in this model has the potential to be reduced to as low as 16% (Zhang et al 2010a). However, treatment with the GSK3b inhibitor had no effect on pTAK1 levels.…”
Section: Discussionmentioning
confidence: 86%
“…Although it is possible that there was a "floor" effect, this is unlikely as the residual infarct was still .30% of the ischemic hemisphere even after combination treatment, due to the length of the occlusion. Infarct in this model has the potential to be reduced to as low as 16% (Zhang et al 2010a). However, treatment with the GSK3b inhibitor had no effect on pTAK1 levels.…”
Section: Discussionmentioning
confidence: 86%
“…In this regard, it has been demonstrated that GPER activation may decrease myocardial damage and increase functional recovery after ischemia-reperfusion (I/R) injury, which often induces dangerous complications like arrhythmia in patients with myocardial infarction (74)(75)(76)(77)(78). Likewise, in rat hearts of both sexes exposed to I/R injury, the activation of GPER reduced myocardial inflammation and infarct size as well as improved immunosuppression and myocardial mechanical performance (79)(80)(81). Interestingly, the expression levels of both GPER and HIF-1α were found to be increased in spontaneously hypertensive rat hearts compared to normotensive controls, suggesting that HIF-1α/ GPER signaling may represent a transduction mediator in certain conditions characterized by elevated blood pressure (74), which is tightly linked to hypoxia (82).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingmentioning
confidence: 99%
“…Conversely, deletion of Gper increases blood pressure (44). G-1 improves functional recovery from myocardial ischemia-reperfusion by reducing post-ischemic contractile dysfunction and infarct size, reduces brain infarct size, and prevents strokeinduced immunosuppression in rats (13,76). However, because of its novelty, the mechanism by which GPER mediates estrogen action is still unclear (38).…”
mentioning
confidence: 99%